INOVASI PENGGUNAAN KONSEP MODULAR FASHION PADA PERANCANGAN BUSANA DEMI-COUTURE DALAM MENGHADAPI ISU OVERCONSUMPTION DI KALANGAN GEN Z: INNOVATION BY USING THE MODULAR FASHION CONCEPT IN DEMI-COUTURE FASHION DESIGN TO FACE THE ISSUE OF OVERCONSUMPTIONAMONG GEN Z - Erica Christiana; Maria Nala Damajanti; Dibya Adipranata Hody (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Innovation By Using The Modular Fashion Concept In Demi-Couture Fashion Design To Face The Issue Of Overconsumption Among Gen Z. The issue of excessive consumption has brought many negative impacts in Indonesia. Fashion design is intended to overcome the problem of excessive consumption among Gen Z which is inﬂuenced by social media trends. The design was made using the design thinking method to ﬁnd out how Gen Z's fashion needs are in dealing with this issue. Data was taken from interviews, journal articles and previous research, and fashion industry reports. The data shows that the modular concept is able to meet the needs of Gen Z by providing many diﬀerent style options in just one outﬁt. In addition, the modular concept is also a unique innovation that can open up new opportunities in the Indonesian fashion industry.